Tanner crab at southwestern Kamchatka: fishing, stock condition and specifics of the assessment - Р. Yu. Ivanov (Известия ТИНРО, 2024)
Results of the current stage of research on tanner crab at the southwestern coast of Kamchatka, harvested in the Kamchatka-Kuril fishing subzone are presented. The stock dynamics since 2001 is analyzed, with special attention to its assessing and forecasting. Features of the crab biology associated with terminal molting are described. The algorithm for separation of the tanner crab recruits into morphometrically mature and immature males is developed that allows to calculate probability for a particular size group of morphometrically immature males to undergo the terminal molt and join to the commercial stock. This algorithm is applied for the data collected at southwestern Kamchatka since 2010. Two peaks in total male abundance of tanner crab were observed in 2005–2006 and 2020–2022. Landing of this species was banned in the Kamchatka-Kuril fishing subzone in 2019–2020, as the result of the local population abundance drop in the previous two years, but was resumed in 2021 after its full restoration. Possible reasons for underestimation of the crab recruitment are discussed, related both with features of the species biology and methodological problems. The population in the Kamchatka-Kuril fishing subzone is currently the most abundant for tanner crab, and this stock in 2020–2022 has reached the historical peak. The fishing of tanner crab in the last three years is distinguished by high catches and high rate of the total allowable catch (TAC) utilization.